2015
DOI: 10.4103/2319-4170.157440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of hippocampal sparing during whole brain radiotherapy on neurocognitive functions: A preliminary report of a prospective phase II study

Abstract: Background: Whole brain radiotherapy (WBRT) is the treatment of choice for patients with brain metastases. However, neurocognitive functions (NCFs) decline due to impaired hippocampal neurogenesis might occur thereafter. It is hypothesized that conformal hippocampal avoidance during the course of WBRT (HA-WBRT) might provide meaningful NCF preservation. Our study aims to demonstrate the impact of delivering HA-WBRT on NCF changes in patients receiving WBRT. Methods:Twenty-five patients who were referred for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The N -methyl- d -aspartate inhibitor memantine has previously shown to improve neurocognitive side effects from whole-brain radiation therapy for patients with overt metastases ( 21 ). Intensity-modulated radiation therapy has also been employed with hippocampal avoidance specifically for the purpose of improving neurocognition ( 22 , 23 ). These strategies have been combined in NRG Oncology CC-001 with the intent of improving quality of life and cognition for patients receiving prophylactic whole-brain radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The N -methyl- d -aspartate inhibitor memantine has previously shown to improve neurocognitive side effects from whole-brain radiation therapy for patients with overt metastases ( 21 ). Intensity-modulated radiation therapy has also been employed with hippocampal avoidance specifically for the purpose of improving neurocognition ( 22 , 23 ). These strategies have been combined in NRG Oncology CC-001 with the intent of improving quality of life and cognition for patients receiving prophylactic whole-brain radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of HA-WBRT in reducing NCD has been assessed in prospective clinical trials, 11 , 12 including RTOG 0933, a Phase II multi-institutional study of HA-WBRT (30 Gy in 10 fractions) for patients with BM. 11 The trial included patients with BMs located outside a 5 mm margin around the hippocampus, with a total of 100 patients analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…With using IMRT, hippocampus can be localized and hence the dentate gyrus can be spared, resulting in prevention or decrease neurocognitive decline to some extent [121]. Lin et al [122] reported significantly lower rates of memory loss posttreatment and with no treatment-related decline in quality of life with IMRT RT.…”
Section: New Treatment Techniquesmentioning
confidence: 99%